Bender-extender elements for characterization of cement paste at early ages - Granja, José Luís Duarte (2016)
The embedment of bender-extender elements in cement-based materials for assessment of the early development of mechanical properties is a relatively unexplored field. This technique provides the opportunity of embedding piezoelectric elements (emitter and receiver) into the tested material at the fresh state, generate waves and assess the velocity of propagation. It has the interesting feature of allowing distinct frequencies of wave to be explored at the several stages of stiffening of the testing material, thus maximising signal intensity and facilitating the identification of velocities. This paper presents an exploratory application of bender- extender elements to cement paste specimens, in parallel with other established experimental techniques, such as the Vicat needle, ultrasound pulse velocity measurements (with external probes), measurement of E-modulus through cyclic compressive testing and continuous assessment of the E-modulus of the cement paste through EMM-ARM. The results are evaluated and discussed in an integrated manner and conclusions are drawn in regard to the potential of using bender-extender elements in cement-based materials